Enhanced calcium solubility of bio-calcium powder from blackchin tilapia (Sarotherodon melanotheron) bone: Influence of alkaline pretreatment conditions - Senphan, Theeraphol; Mungmueang, Natthapong; Sazedul Hoque, Md; Sriket, Chodsana; Benjakul, Soottawat; Kittiphattanabawon, Phanat; Sinthusamran, Sirima (My University, 2026)
Bio-calcium powder was prepared from blackchin tilapia ( Sarotherodon melanotheron ) bones, an invasive species by-product from surimi production in Thailand, to evaluate the effects of alkaline pretreatment on bio-calcium properties. Bones were pretreated with NaOH or KOH (1 and 2 M) at a bone-to-solution ratio of 1:10 (w/v) for 2 h, followed by ethanol washing, hydrogen peroxide bleaching, drying, and grinding to obtain bio-calcium powder. The yield on a wet weight basis was 26–28%, with water activity values of 0.33–0.34 measured at room temperature. Among all treatments, 1 M KOH gave the highest yield (28%), calcium content (26.13%), and lightness (L∗ = 88.5). Collagenous proteins and hydroxyapatite were identified by SDS-PAGE and ATR-FTIR, respectively. All bio-calcium samples showed four to five times higher in vitro calcium solubility after simulated gastrointestinal digestion (13.4-17.50%) than calcium carbonate (3.4%). The 2 M treatments exhibited the highest calcium solubility (17.2-17.50%). The 1 M KOH can be used for food fortification due to its high yield and lightness, whereas the 2 M treatments can serve as calcium supplements where higher calcium solubility is required. Blackchin tilapia bone is a potential source for bio-calcium production, with 1 M KOH suitable for food fortification and 2 M treatments more appropriate for applications requiring higher calcium solubility.
Keywords: Alkaline pretreatment; Bio-calcium; Blackchin tilapia; Fish bone; In vitro calcium solubility; Invasive species